2016
DOI: 10.1038/srep29920
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms as a side effect of Interferon-α therapy induced by induction of indoleamine 2,3-dioxygenase 1

Abstract: Depression is known to occur frequently in chronic hepatitis C viral (HCV) patients receiving interferon (IFN)-α therapy. In this study, we investigated whether indoleamine 2,3-dioxygenase1 (IDO1)-mediated tryptophan (TRP) metabolism plays a critical role in depression occurring as a side effect of IFN-α therapy. Increases in serum kynurenine (KYN) and 3-hydroxykynurenine (3-HK) concentrations and in the ratios of KYN/TRP and 3-HK/kynurenic acid (KA) were much larger in depressive HCV patients than in non-depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 61 publications
2
40
0
Order By: Relevance
“…Elevated DO activity ( Kynurenine Pathway activation) is linked to both human depression and murine depression-like symptomology (Baranyi et al, 2015; Murakami et al, 2016; O’Connor et al, 2009b; O’Connor et al, 2009c). Although the Kynurenine Pathway is associated with depression, there has been no work suggesting that anti-depressant activity involves modulation of the Kynurenine Pathway .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Elevated DO activity ( Kynurenine Pathway activation) is linked to both human depression and murine depression-like symptomology (Baranyi et al, 2015; Murakami et al, 2016; O’Connor et al, 2009b; O’Connor et al, 2009c). Although the Kynurenine Pathway is associated with depression, there has been no work suggesting that anti-depressant activity involves modulation of the Kynurenine Pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that Ido1 in dendritic (Munn et al, 2002) and NK cells (Kai et al, 2004) produce Kyn to modulate the peripheral immune system (Lippens et al, 2016; Maldonado and von Andrian, 2010; Munn et al, 2002; Murakami et al, 2013). Clinical studies suggest a link between this response and depression (Baranyi et al, 2015; Murakami et al, 2016), connecting peripheral DO activity and MDD. Since Ido1-FL expression by PBMCs was increased in response to LPS ( in vivo ) and IFNγ ( ex vivo ) and blocked by Desip, our work clearly shows that Desip diminishes both CNS and peripheral DO expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations